2,4-D and IAA Amino Acid Conjugates Show Distinct Metabolism in Arabidopsis - Eyer, Luděk; Vain, Thomas; Pařízková, Barbora; Oklestkova, Jana; Barbez, Elke; Kozubíková, Hana; Pospíšil, Tomáš; Wierzbicka, Roksana; Kleine-Vehn, Jürgen; Fránek, Milan; Strnad, Miroslav; Robert, Stéphanie; et al. (PLOS ONE, 2016)
The herbicide 2,4-D exhibits an auxinic activity and therefore can be used as a synthetic and traceable analog to study auxin-related responses. Here we identified that not only exogenous 2,4-D but also its amide-linked metabolite 2,4-D-Glu displayed an inhibitory effect on plant growth via the TIR1/AFB auxin-mediated signaling pathway. To further investigate 2,4-D metabolite conversion, identity and activity, we have developed a novel purification procedure based on the combination of ion exchange and immuno-specific sorbents combined with a sensitive liquid chromatography-mass spectrometry method. In 2,4-D treated samples, 2,4-D-Glu and 2,4-D-Asp were detected at 100-fold lower concentrations compared to 2,4-D levels, showing that 2,4-D can be metabolized in the plant. Moreover, 2,4-D-Asp and 2,4-D-Glu were identified as reversible forms of 2,4-D homeostasis that can be converted to free 2,4-D. This work paves the way to new studies of auxin action in plant development.